Perancangan Active Database System pada Sistem Informasi Pelayanan Harga Pasar - Sucipto, Sucipto (Universitas Nusantara PGRI Kediri, 2017)
Information system is a system related to the existence of programming and database. A good information system is dynamic. Dynamic information systems can not be separated with the existence of databases as data storage. In general, the database is used passively so that its function is only for data storage, but the database also can be as a control system information. Some opensource databases already support for system control or that can be called active database system such as MySQL, MariaDB and PosgreSQL. Active database system provides database function to get reactive behavior and control system information at database level. Business processes that are typically performed by programming languages ​​as a rule incorporated in the application can be entered directly into the database. This research is done for the design of an active database system against market price services. This active database system approach is designed to get an applicative and responsive service system to collaborate with the control system on the modem.